Educational workshop with adolescents on leprosy: case report - Bruna Hinnah Borges Martins de Freitas; Fabiane Blanco e Silva; Hellen Cristina Dias dos Santos Silva; Alan Maique Ribeiro Fernandes da Costa; Karine Ferreira da Silva; Sabrina Edvirges Garcia Silva
ABSTRACT Objective: To report the experience of professors and students in the development and implementation of an educational workshop on leprosy with adolescents. Method: This is a case report from actions contained in a university extension project. Results: The workshop program was elaborated with duration of two hours, including five dynamic techniques adapted to the topic: adjective, face, traffic light, true or false and mosaic. It was verified that the construction of knowledge in light of the verbalization of the adolescents and the interest in working in the society they live through sharing this knowledge, especially those who were more involved in the process. Conclusion: It was concluded that the applied workshops enabled building knowledge and demystifying myths and stigmas socially constructed to adolescents, as well as allowed Nursing students to experience educational interventions on leprosy with adolescents.